Evaluation of spin in the abstracts of systematic reviews and meta-analyses relating to postoperative nausea and vomiting. Issue 8 (5th August 2022) - Bruns, Matthew; Manojkumar, Arvind; Ottwell, Ryan; Hartwell, Micah; Arthur, Wade; Roberts, Will; White, Brad; Young, Jeff; Martin, Janet; Wright, Drew N.; Chen, Suhao; Miao, Zhuqi; et al.
Abstract : INTRODUCTION: Spin – the beautification of study results to emphasise benefits or minimise harms – is a deceptive reporting strategy with the potential to affect clinical decision-making adversely. Few studies have investigated the extent of spin in systematic reviews. Here, we sought to address this gap by evaluating the presence of the nine most severe forms of spin in the abstracts of systematic reviews on treatments for postoperative nausea and vomiting (PONV). PONV has the potential to increase hospital costs and patient burden, adversely affecting outcomes. METHODS: We developed search strategies for MEDLINE and Embase to identify systematic reviews focused on PONV. Following title and abstract screening of the reviews identified during the initial search, those that met inclusion criteria were evaluated for the presence of spin and received a revised AMSTAR-2 (A Measurement Tool to Assess Systematic Reviews) appraisal by two investigators in a masked, duplicate manner. Study characteristics for each review were also extracted in duplicate. RESULTS: Our systematic search returned 3513 studies, of which 130 systematic reviews and meta-analyses were eligible for data extraction. We found that 29.2% of included systematic reviews contained spin (38/130). Eight of the nine types of spin were identified, with spin type 3 ('selective reporting of or overemphasis on efficacy outcomes or analysis favouring the beneficial effect of the experimental intervention') being the most common. Associations were found between spin and funding source. Spin was more likely in the abstracts of privately funded than nonfunded studies, odds ratio (OR) 2.81 [95% confidence interval (CI), 0.66 to 11.98]. In the abstracts of studies not mentioning funding spin was also more likely than in nonfunded studies, OR 2.30 (95% CI, 0.61 to 8.70). Neither of these results were statistically significant. Significance was found in the association between the presence of spin and AMSTAR-2 ratings: 'low' quality studies were less likely to contain spin than 'high' quality, OR 0.24 (95% CI, 0.07 to 0.88): 'critically low' studies were also less likely to contain spin than 'high' quality studies, OR 0.21 (95% CI, 0.07 to 0.65). There were no other associations between spin and the remaining extracted study characteristics or AMSTAR-2 ratings. CONCLUSION: Spin was present in greater than 29% of abstracts of systematic reviews and meta-analyses regarding PONV. Various stakeholders must take steps to improve the reporting quality of abstracts on PONV.